Spodocybe umbilicata (Hygrophoraceae, Agaricales), a newly discovered species from subtropical China - Xiao, Ying-Qun; Li, Hai-Jiao; Li, Sai-Nan; Chen, Zuo-Hong; Zhang, Ping; He, Zheng-Mi (Phytotaxa, 2023)
Spodocybe is a recently established genus with many potential species yet to be discovered. The present study reports a new species of Spodocybe collected from subtropical China, whose delimitation is supported by both morphological and phylogenetic evidence. The species is characterized by its small umbilicate pileus with a greyish brown, finely felty surface, white decurrent lamellae, finely fibrillose stipe concolorous with the pileal surface, and elongate to cylindrical basidiospores measuring 6.0–9.0 × 3.0–4.5 μm. In addition, a worldwide key to the known Spodocybe species is provided.